Do 'virtual postcards' enhance blended learning?. (14th January 2020) - Harris, Dylan; Rawlinson, Fiona
Summary: Background: In the traditional 'postcard' educational technique, learners write learning points on a postcard at the end of a face‐to‐face teaching session. The teacher subsequently posts them back to the learners in order to remind and reinforce learning. Cardiff University's Palliative Care Masters programme adapted the traditional postcard technique to suit a modern blended learning course, introducing the concept of 'virtual postcards'. Methods: Students were asked to complete a postcard for face‐to‐face teaching sessions on 'symptom control' and were free to use their postcard as they wished, e.g. to draw pictures, to list key bullet points, etc. A selection of postcards were subsequently scanned and uploaded into the corresponding online module. These were visible to all students so that they could learn from each other's virtual postcards. Results: Most students felt that the virtual postcards were a useful learning material (12% did not). Around half of the students felt that having a selection of the virtual postcards was preferable to all of them being uploaded (52%; 28% expressed no preference). Students were divided as to whether this would have become too monotonous to repeat for all topics in face‐to‐face teaching (40% felt that these should just be used for some topics, 18% had no preference, and 42% felt that these would be useful for all topics). Discussion: In general, the students found virtual postcards useful as part of blended learning, and liked learning from other people's virtual postcards as well as from their own. There needs to be a balance between how often the technique is employed, and how many postcards are uploaded, to avoid information overload and losing value.